Desbalanço autonômico e alterações metabólicas em adolescentes obesos - Hussid, Maria Fernanda (2020)
INTRODUCTION: The prevalence of obesity in childhood and adolescence reached a pandemic level, leading to an increase in Metabolic Syndrome (MetS), arterial hypertension (AH) and obstructive sleep apnea (OSA). Obesity, OSA and AH independently share the same pathophysiological factors, including endothelial dysfunction, sympathetic hyperactivation and decreased baroreflex sensitivity. In a previous study, we observed that obese adolescents have endothelial dysfunction, having as predictor variables of decreased flow-mediated dilation (FMD), waist circumference (WC) and systolic blood pressure (SBP). It is not known whether, in addition to endothelial dysfunction, autonomic changes would be involved in the increase in BP in obese adolescents. OBJECTIVES: To analyze the autonomic mechanisms involved in the increase in blood pressure in obese adolescents, and the associated risk factors. METHODS: 25 Obese adolescents of both sexes and 14 Eutrophic adolescents (13.5 [13.0 - 15.8] and 14 [14 - 15.5] years old, respectively; P = 0.055), paired by sex, pubertal staging and height. Anthropometric data, body composition, risk factors for MetS (International Diabetes Federation), functional capacity assessed by the cardiopulmonary exercise test (VO2 peak), vascular function by FMD and OSA through the apnea-hypopnea index (AHI) and of minimum oxygen saturation (Min O2 Sat) on polysomnography were studied. Spectral analysis method was used for non-invasive assessment of the autonomic nervous system. The BP and HR signals were recorded using Finometer® and electrocardiogram, respectively, obtaining a tachogram and a sistogram using Windaq® software. Subsequently, such data were analyzed by Cardioseries® software, being evaluated R-R interval (time domain) and the predetermined frequency bands: low frequency (LF; sympathetic activity) between 0.04 and 0.15 Hz and high frequency (HF; parasympathetic activity) between 0.15 and 0.4 Hz. Relation LF / HF was calculated for the assessment of sympathetic-vagal balance. Baroreflex was calculated using the square root of the ratio between absolute LF (FC) / absolute LF (PAS). RESULTS: Obese adolescents presented increased weight values (100 ± 19.3 vs. 55 ± 8.0 kg; P <0.001), WC (105.2 ± 13.0 vs. 70.0 ± 6.2 cm; P <0.001), percentage of fat mass (40.8 ± 6.3 vs 17.0 ± 10.0; P <0.001), SBP (118.9 ± 10.2 vs 106.4 ± 7.2 mmHg; P <0.001) and DBP, in addition to higher levels of triglycerides, LDL-c and lower HDL-c, compared to Eutrophic. 36% of the Obese and 0% of the Eutrophic presented SMet. In addition, Obese patients had lower VO2peak (25.0 ± 5.8 vs. 32.2 ± 7.8 mL O2/kg/min; P = 0.013) and, although there was no difference in AHI, they had lower levels of Min O2 Sat on polysomnography (P = 0.016). In vascular evaluation, Obese patients had lower FMD than the Eutrophic ones (6.2% ± 2.8% vs. 12.5% ± 8.3%; P = 0.005). In spectral assessment of heart rate (HR), Obese patients had higher mean HR (P = 0.010), lower R-R interval (P = 0.010), higher LF (P = 0.027), lower HF (P = 0.030) and greater sympathetic-vagal balance (LF/HF; P = 0.024). In spectral analysis of BP, Obese adolescents had higher mean SBP (P = 0.047) and greater BP variance (P = 0.030) compared to normal weight. However, there was no difference in baroreflex sensitivity between 2 groups. In subsequent analyzes, it was observed that the percentage of fat mass showed a strong correlation with sympathetic-vagal balance (R = 0.476; P = 0.009) and with R-R interval (R = -0.551; P = 0.002), as well as WC was related to sympathetic-vagal balance (R = 0.399; P = 0.021). CONCLUSION: Obese adolescents have increased sympathetic activity and decreased parasympathetic activity. Sympathetic-vagal imbalance seems to be an important mechanism involved in increasing blood pressure levels in obese adolescents. However, in this early stage of obesity, there is still no decrease in baroreflex sensitivity. The increase in body fat seems to be the trigger for autonomic dysfunction in obese adolescents.